2004
DOI: 10.1021/jp0493226
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Production from Water over M-Doped La2Ti2O7 (M = Cr, Fe) under Visible Light Irradiation (λ > 420 nm)

Abstract: In the search for efficient photocatalysts working under visible light, we have investigated the effect of cation substitution on a layered perovskite, La2Ti2O7. Among various metal dopants, only Cr and Fe induced intense absorption of visible light (lambda > 400 nm), and only these catalysts produced H2 photocatalytically from water in the presence of methanol under visible light irradiation (lambda > 420 nm). The polymerized complex method was found to be more efficient for fabrication of the present catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(115 citation statements)
references
References 30 publications
5
108
1
1
Order By: Relevance
“…To enhance visible light absorption, metal elements are used to dope into La 2 Ti 2 O 7 by tuning the band gap levels to significantly narrow its band gap. Hwang et al reported that transition metal‐doped La 2 Ti 2 O 7 such as Cr or Fe has visible light absorption because their 3d states appeared in the band gap 52. Similarly, Kim et al reported that alkaline earth metal‐doped La 2 Ti 2 O 7 such as Ba, Sr or Ca remarkably enhanced the photocatalytic activity for water splitting reaction 53.…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…To enhance visible light absorption, metal elements are used to dope into La 2 Ti 2 O 7 by tuning the band gap levels to significantly narrow its band gap. Hwang et al reported that transition metal‐doped La 2 Ti 2 O 7 such as Cr or Fe has visible light absorption because their 3d states appeared in the band gap 52. Similarly, Kim et al reported that alkaline earth metal‐doped La 2 Ti 2 O 7 such as Ba, Sr or Ca remarkably enhanced the photocatalytic activity for water splitting reaction 53.…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…It has been sought recently to be an effective matrix for doping to achieve improved electrical properties. 11 Doped perovskites, [12][13][14][15][16][17][18] by virtue of band gap tuning and consequent redshift in optical absorption of the UV-active original host matrix, have been shown to possess potential applications in visible light photocatalysis and solar energy conversion. Such doping is therefore very interesting in view of the need of efficient photoactive materials for solar energy conversion applications.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there are several reports on the anionic and cationic substitution of metal ions in the host lattice to reduce the BG. 4,5 Here, we systematically attempt Pb substitution at the B site in cubic BaSnO 3 and further study its effect on the physicochemical properties of obtained BaPb x Sn 1−x O 3 . Thus, BaPb x Sn 1−x O 3 was chemically synthesized and calcined at a much lower temperature than 1000°C.…”
Section: Eco-friendly Catalysis and Energy Laboratory (Nrl) Departmementioning
confidence: 99%
“…BaPb x Sn 1−x O 3 samples were synthesized by a modified citrate complex method, 5 in which typically ͑say, for BaPb 0.5 Sn 0.5 O 3 ͒ 20 mmol of Ba͑NO 3 ͒ 2 , 10 mmol of Pb͑CH 3 CO 2 ͒ 4 and SnCl 4 ·SH 2 O 1 , 0.4 mol ethylene glycol, and 0.1 mol of citric acid were mixed and stirred at 60°C. The thus obtained thick yellow gel was heated for more than 10 h at 130-140°C to obtain brown color gel, and later to 350°C for 8 h and 700°C for 10 h to obtain the oxide.…”
Section: Eco-friendly Catalysis and Energy Laboratory (Nrl) Departmementioning
confidence: 99%